Fabrication of 1, 1-Dimethylhydrazine Gas sensor Based on Nano Structure Conducting Polyaniline - S. Pirsa (Journal of Sciences, Islamic Republic of Iran)
Determination of 1, 1-dimethylhydrazine (DMH) in air is carried out by spectrophotometry, GC or HPLC analysis, but in this study DMH was analyzed by a gas sensor based on nanostructure conducting polyaniline. Determination of DMH has been done very simplely and quickly in recent work. Electrically conductive fibers have been prepared by polymerization of aniline on surfaces of commercial polymer fibers in the presence of an oxidizing agent. The resistance of poly aniline (PANI) coated fiber sensor (PANI-FS) was investigated and related to coating conditions, which was controlled by adjusting the reactant concentrations. The morphology of the conducting film on the surface of the fibers was examined by scanning electron microscope (SEM). The sensing behavior of PANI in the presence of some volatile organic compounds (VOCs) is studied experimentally. The PANI sensor had demonstrated to have good sensitivity for DMH and good reproducibility when reused.